Human Resource Capacity Development Supports Procurement Functional Position Fulfillment: Pengembangan Kapasitas Sumber Daya Manusia Mendukung Pemenuhan Posisi Fungsional Pengadaan - siti zulaikah; Isna Fitria Agustina (Academia Open, 2025)
General Background: Human resource capacity development is essential for ensuring professional, transparent, and accountable government procurement processes. Specific Background: In Sidoarjo Regency, the limited number and competence of procurement personnel have created challenges in fulfilling functional procurement management positions despite regulatory requirements for standardized qualifications and competencies. Knowledge Gap: Previous studies emphasized performance improvement and competency-based management but provided limited analysis of human resource capacity development as a strategy to fulfill procurement functional position formation at the local government level. Aims: This study analyzes human resource capacity development efforts to support the fulfillment of procurement functional positions in Sidoarjo Regency by evaluating personnel quantity, competence, and competency gaps. Results: Using a qualitative descriptive approach, findings indicate that capacity development is implemented through formal education encouragement for employees lacking bachelor’s degrees, participation in webinars, technical training, and competency testing, as well as work experience assignments as procurement officials or selection working group members. However, participation in competency testing remains constrained by cost, time limitations, and employee readiness, and the number of functional procurement officials remains below the recommended requirement. Novelty: This study provides an integrated analysis linking education, skills training, and professional experience as key indicators for fulfilling procurement functional position formation within a regional government context. Implications: The findings provide empirical evidence to support policy formulation for systematic human resource capacity development to reduce competency gaps, improve personnel availability, and support accountable government procurement administration. Highlights: Formal Higher Education Pathways Are Encouraged to Meet Minimum Qualification Requirements for Procurement Personnel. Training Participation and Certification Opportunities Remain Constrained by Budget Allocation, Workload, and Readiness Factors. Task Distribution as Selection Working Group Members and Procurement Officials Provides Practical Professional Skill Accumulation. Keywords: Human Resource Capacity Development, Functional Procurement Positions, Government Procurement Personnel, Competency Gaps, Public Procurement Management